(untitled) (Clinical Sociology Review, 2023)
Building on the mission of Quebec schools which consists of educating, socializing and qualifying, the PhiloJeunes project, established in Quebec since 2015, works to strengthen protective factors in the face of violent radicalization through the implementation of a philosophical practice in class. This article is based on a qualitative study carried out with teachers involved in this educational project, in order to explore their experience during the training and application of said project. The analysis highlights the challenges and levers encountered by educators, particularly with regard to a certain normative prescription/proscription regarding the expression and circulation of emotions. The inevitable overlap between the rational sphere and the emotional sphere leads the authors to support, in the vein of the legacy of John Dewey, an overcoming of this outdated opposition, in order to embrace a sensitive democratic education which can promote the realization of objectives of preventing violent radicalization through philosophical discussion in a school context.